Pelatihan Pembuatan Konten Promosi Wisata dalam Rangka Penguatan Kapasitas Pengetahuan dan Keterampilan Kelompok Perhutanan Sosial dalam Pengelolaan Potensi Wisata di Kabupaten Garut - Yulia, Iis Anisa; Setyaningsih, Luluk; Anen, Nengsih; Sasongko, Dwi Agus; Mutmainah, Isbandriyati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Social forestry is a sustainable forest management system implemented in state forest areas or private forests. Local communities or customary law communities implement customary forests as the main actors in improving their welfare. The Social Forestry Program aims to enhance community welfare through empowerment patterns while still being guided by sustainability aspects. Communities around forests are given equal and broadest opportunities to apply for forest area management rights to the government. Communities can cultivate and benefit from forests in environmentally friendly ways. One way to utilize forest areas is to make them tourist attractions. Good management of tourist attractions requires skills in planning and implementation. Garut Regency is one area that has many sustainable forest locations that have been used as tourist locations and have the potential to increase people's income, but these tourist attractions still need to bestill need to be well promoted to the wider community. Therefore, training in creating tourism promotional content is required in order to strengthen the knowledge and skills capacity of social forestry groups in managing tourism potential in the Garut Regency. This community service activity aims to increase the knowledge and skills capacity of the Forest Farmers Group (KTH) in creating promotional content for tourist attractions. The result of this activity is that KTH members are able to create promotional content for tourist attractions using the Canva and CapCut applications so that they can increase the number of visitors to their tourist attractions.